(untitled) (Research, Society and Development, 2022)
This paper aims to provide a bibliometric analysis of the literature on oral and maxillofacial surgery, comparing different databases and discussing the advantages, disadvantages, and specific features of each one. A bibliographical search for oral and maxillofacial surgery literature was conducted on Pubmed, Scopus, Web of Science, Dimensions, SciELO, LILACS, and Google Scholar. Seven different search strategies were used on each database. VOSViewer and Microsoft Excel were used for tabulation and data visualization. Some statistical tests were performed with a 95% confidence interval, which was considered significant. A table comparing the number of articles obtained during seven different literature searches was created. A correlogram created in RStudio showed the correlation between the number of articles in the different databases evaluated. The functionalities of each database were compared. It is recommended to use more than one database when searching for literature related to surgery. Among the analyzed databases, PubMed stands out for its functionalities, precision, and quantity of available articles.